THE EFFECT OF PRODUCT QUALITY FOR INCREASE CONSUMER SATISFACTION AT SHOE AND SANDAL STORES IN BOGOR REGENCY - Alwan Abidin Abidin; Muratin Muratin; Muhammad Irfan Rahadian Rahadian (ABNUS Publisher, 2022)
The aims of this study are (1) to find out whether product quality is related and has an effect to consumer satisfaction. This type of quantitative descriptive research with a questionnaire as a data source. The population in this study is the number of consumers who buy shoes and sandals in Bogor for one year, namely in 2021, selling 12,775 people. The sample in this study was 92 respondents, the sampling used was accidental sampling, which is the technique of making a sample based on coincidence, that is, anyone who coincidentally meets a researcher who is buying at a shoe and sandal shop in Bogor is used as a sample. The analytical tool in this research is simple linear regression.